The topochemical reduction of some complex iridium oxides - Murrell, J (2024)
The work presented in this thesis focuses on the topochemical reduction of Ir-containing oxides with perovskite-type structures to form novel anion-deficient and mixed-anion phases. Reactions between n = 1 Ruddlesden-Popper LaxSr4−xCoIrO8 (0 ≤ x ≤ 2) phases and LiH yields the formation of a series of oxyhydride phases, which represent the first oxyhydrides containing a 5d transition metal. For the Sr-rich members of the series (x = 0, 0.5), the extent of oxide-to-hydride exchange is limited by the stability of the overall Ruddlesden-Popper framework and, therefore, the temperature at which the reaction can be performed. Meanwhile, the extent of anion exchange in the remaining members of the series is limited by the formation of the CoI/IrIII oxidation state combination, as reduction of octahedrally-coordinated iridium below IrIII would require occupation of a strongly antibonding eg orbital. Similarly, reaction of LaSr3NiIrO8 with LiH yields the formation of LaSr3NiIrO5.4H2.6, which contains nickel as NiI/II and iridium as IrIII. Whilst iridium is present in its lowest energetically accessible oxidation state, it is not possible to fully reduce nickel to NiI without the onset of non-topochemical decomposition. In an attempt to prepare an analogous anion-deficient phase, LaSr3NiIrO8 was reacted with a Zr getter, which yielded LaSr3NiIrO6.4. This adopts an infinite-chain type structure, which contains IrII that is likely to be disproportionated into IrI and IrIII. Reaction of Sr4MnIrO8 with CaH2 and LiH yields the oxyhydride phases, Sr4MnIrO6.58H1.42 and Sr4MnIrO5.32H2.68, respectively. Whilst the hydride ions are exclusively located at the equatorial positions in Sr4MnIrO6.58H1.42, consistent with the other phases discussed in this thesis, hydride ions are also located at the axial positions in Sr4MnIrO5.32H2.68. This is attributed to a combination of factors, including the strong Jahn-Teller effect associated with MnIII, the tendency for hydride ions to adopt cis-arrangements with respect to each other and the preference for iridium to adopt highly symmetric coordination environments. To explore the reactivity of other Ir-containing phases with LiH, reactions were performed using the 6H-hexagonal perovskite phase, Ba3CoIr2O9, and the double perovskite LaxSr2−xCoIrO6 (x = 0, 1) phases. This yielded the oxyhydride phases, Ba3CoIr2O6.2H2.8 and LaxSr2−xCoIrO4.4H1.6, in which the extent of anion exchange is limited by the stability of the perovskite frameworks, rather than the obtainment of the CoI/IrIII oxidation state combination. Whilst the LaxSr2−xCoIrO4.4H1.6 phases adopt anion-disordered arrangements, Ba3CoIr2O6.2H2.8 adopts a partially anion-ordered arrangement, in which the hydride ions are preferentially located at the corner-sharing sites and adopt a trans-arrangement with respect to each other to optimise the π-bonding interactions. To investigate the reactivity of the LaxSr2−xCoIrO6 phases further, they were heated in the presence of a Zr getter. This led to the formation of LaxSr2−xCoIrO4 infinite-layer phases, which occurs via LaxSr2−xCoIrO5 intermediates. Below 135−140 K, Sr2CoIrO4 adopts a ‘type I’ antiferromagnetic state at the cobalt sites, with very little ordering at the iridium sites. Meanwhile, LaSrCoIrO4 adopts a magnetic structure based on C-type antiferromagnetic ordering with a possible incommensurate modulation that could arise from spin canting. Finally, the effect of ball-milling on the reactivity of the perovskite phase, La2CoRhO6, was investigated. Whilst ball-milling showed no enhancement in reactivity for the reaction between La2CoRhO6 and NaH, reaction of the ball-milled sample with LiH allowed a greater extent of oxide-to-hydride exchange to be achieved. This was attributed to the fact that the oxyhydride product arising from the reaction with LiH is intrinsically highly strained, so ball-milling destabilises the starting material to a greater extent than the oxyhydride product.